2020
DOI: 10.3758/s13421-019-00992-8
|View full text |Cite
|
Sign up to set email alerts
|

Concreteness and disagreement: Comment on Pollock (2018)

Abstract: y, Pollock, 2018) points out that most memory experiments using abstract and concrete words have a potential confound: Raters express more disagreement, on average, about the rating for an abstract word than for a concrete word, as evidenced by the larger standard deviation of the rating (SDR). Therefore, past demonstrations of the concreteness effect could be explained by the disagreement hypothesis: Words that engender disagreement (i.e., have a larger SDR) are more difficult to remember than those that enge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…One concern with our results may be that when two sets of stimuli are equated on so many dimensions, as was the case in our experiments, the one remaining dimension on which they differ will no longer be sufficient to produce an effect. Although this is possible and cannot be ruled out for our data, we do note that a number of other studies using similarly highly controlled stimuli have found effects of frequency (Neath & Surprenant, 2019), concreteness (Neath & Surprenant, 2020), neighbourhood size (Guitard, Gabel, Saint-Aubin, Surprenant, & Neath, 2018), and visual similarity (Chubala, Guitard, Neath, Saint-Aubin, & Surprenant, 2020) in serial recall tests.…”
Section: Discussionmentioning
confidence: 68%
“…One concern with our results may be that when two sets of stimuli are equated on so many dimensions, as was the case in our experiments, the one remaining dimension on which they differ will no longer be sufficient to produce an effect. Although this is possible and cannot be ruled out for our data, we do note that a number of other studies using similarly highly controlled stimuli have found effects of frequency (Neath & Surprenant, 2019), concreteness (Neath & Surprenant, 2020), neighbourhood size (Guitard, Gabel, Saint-Aubin, Surprenant, & Neath, 2018), and visual similarity (Chubala, Guitard, Neath, Saint-Aubin, & Surprenant, 2020) in serial recall tests.…”
Section: Discussionmentioning
confidence: 68%
“…4The abstract and concrete words did differ in the mean standard deviation of the concreteness rating; however, Neath and Surprenant (2020) have shown this dimension does not affect the concreteness effect, at least in serial recall.…”
mentioning
confidence: 92%
“…The word tilth was omitted from the low-frequency pool because it was not in any of the databases and because none of the authors knew what it meant.4 The abstract and concrete words did differ in the mean standard deviation of the concreteness rating; however,Neath and Surprenant (2020) have shown this dimension does not affect the concreteness effect, at least in serial recall.STIMULUS-BASED MIRROR EFFECTS REVISITED…”
mentioning
confidence: 99%
“…E.g. it is assumed that concreteness influences learning, recognition memory and the speed of visual recognition, reading and spelling (Spreen and Schulz, 1966;Hargis and Gickling, 1978;Sadoski et al, 2004;Palmer et al, 2013;Neath and Surprenant, 2020). Moreover, studies conducted on abstract and concrete words also found that the participants remembered concrete words better than the abstract words (for an overview of various studies see e.g.…”
Section: Concretenessmentioning
confidence: 99%